I am somebody! : a biography of Jesse Jackson - Haskins, James, 1941- (Hillside, N.J., U.S.A. : Enslow Publishers, 1992)
Presents the life, accomplishments, and goals of the civil rights activist and politician Jesse Jackson, from his childhood in North Carolina through his years in Chicago and Washington, D.C.
Includes bibliographical references (p. 107-110) and index.
13
Keywords: Jackson, Jesse, -- 1941-; Jackson, Jesse, -- 1941- -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; Presidential candidates -- United States -- Biography -- Juvenile literature; Afro-Americans -- Biography; Civil rights workers; African Americans -- Biography -- Juvenile literature